The Influence of System Security and Sharia Compliance on User Loyalty in Financial Technology Applications - Muhibbatul Khoiriyyah; Eka Sutisna; M Gelar Faisal (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the effect of system security and sharia compliance on user loyalty of sharia-based fintech applications in Indonesia. A quantitative approach is used with a survey method of 130 respondents who are active users of sharia fintech applications. The instrument in the form of a Likert-scale questionnaire was analyzed using the SEM-PLS technique. The results showed that system security and sharia compliance had a positive and significant effect, both partially and simultaneously, on user loyalty. High system security, such as data protection and authentication, as well as compliance with sharia principles such as contract transparency and Sharia Supervisory Board supervision, are proven to build trust and increase user attachment to the application. These findings contribute to the development of strategies to increase customer loyalty in Islamic fintech in Indonesia.